Effect of cochlear implantation on vestibular function in children: A scoping review - Gerdsen, Max; Jorissen, Cathérine; Pustjens, Daphne Catharina Francisca; Hof, Janke Roelofke; Van Rompaey, Vincent; Van De Berg, Raymond; Widdershoven, Josine Christine Colette (Frontiers in Pediatrics, 2022)
Objective To provide a scoping review of the available literature for determining objectively the effect of cochlear implantation on vestibular function in children. Methods A literature search was performed and the following criteria were applied: vestibular tests that were performed on subjects within the range of 0–18 years old before and after cochlear implantation. The papers conducted at least one of the following tests: (video) head impulse test, caloric test, cervical and ocular vestibular evoked myogenic potentials or rotatory chair test. Included papers underwent quality assessment and this was graded by risk of bias and directness of evidence. Results Fourteen articles met the selection criteria. The included studies showed that cochlear implantation leads to a decrease in vestibular function in a proportion of the patient population. This loss of vestibular function can be permanent, but (partial) restoration over the course of months to years is possible. The pooling of data determined that the articles varied on multiple factors, such as time of testing pre- and post-operatively, age of implantation, etiologies of hearing loss, used surgical techniques, type of implants and the applied protocols to determine altered responses within vestibular tests. The overall quality of the included literature was deemed as high risk of bias and medium to low level of directness of evidence. Therefore, the data was considered not feasible for systematic analysis. Conclusion This review implicates that vestibular function is either unaffected or shows short-term or permanent deterioration after cochlear implantation in children. However, the heterogeneity of the available literature indicates the importance of standardized testing to improve our knowledge of the effect of cochlear implantation on the vestibular function and subsequent developmental consequences for the concerned children.